PERILAKU NGEREMAN HASIL TAMBANG TIMAH DI PERAIRAN PANTAI TAKARI, DESA REBO, KABUPATEN BANGKA, PROVINSI KEPULAUAN BANGKA BELITUNG - Dersi Herka Mayu; Kurniawan Kurniawan (Sabda: Jurnal Kajian Kebudayaan, 2019)
Takari coastal water has the potential to use natural resources which are rich in lead content. This potential is utilized by the community as one of the occupational professions known as tin mining or tin mining activities. The term ngereman appears as a custom of tradition that has been going on for generations, namely asking for a 'quota' in the form of tin which is carried out during tin mining activities in an area. The results showed that the average 'ngereman' actor in Takari coastal waters was dominated by women, with 'widow' status based on economic aspects in meeting economic needs, whose generally limited expertise, education and economic access. This phenomenon of gluing in interaction with the miners is based on two things, the first by bringing the miner's food needs and the second without bringing the miner's needs to only expect compassion or voluntary deed from the miners. The granting of ‘quota’ for mining products is based on two considerations, namely if there are tin products obtained for sale and not harming the miners themselves, without any element of violence.